Secondary Glaucoma due to Mucopolysaccharodis: a Case Report - Mulyadi, Irene Carolin; Franky Richard Kasih (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2025)
Introduction: Mucopolysaccharidosis (MPS) is a rare, autosomal recessive inherited lysosomal storage disorder involved in glycosaminoglycans (GAG) degradation. Glaucoma, as a leading cause of irreversible blindness, in MPS patients has a very low occurrence rate, indicating that this condition needs attention and more research to improve MPS patients’ quality of life. Case Report: A 15-year-old boy came with a chief complaint of progressive onset of blurred vision in both eyes 4 years prior to admission. He was being treated as hypermetropia since then. Opacity was noticed in both eyes in addition to deteriorating vision for the last 3 months. Genetic test supported the possibility of MPS type VI. Hence this patient was diagnosed as secondary glaucoma due to MPS. Glaucoma medications were unable to control the intraocular pressure, thus trabeculectomy was planned. After the surgery, the patient was given antibiotic, analgetic, steroid, and anti-glaucoma medications. Releasable suture was removed on the 14th day post-surgery due to elevated IOP. Unfortunately, the patient did not make any visit afterward for further follow-up. Discussion: Our case faces several difficulties with anterior and posterior ophthalmological examinations. Corneal opacity with corneal thickening often occurs in MPS type VI. The exact mechanisms underlying corneal opacities remain elusive. IOP measurements can be helpful for the diagnosis and monitoring of glaucoma. Changes in corneal thickness can affect IOP measurements, and corneal opacity can prevent accurate visualization of the optic nerve and cornea-sclera angle, as well as supportive diagnostic devices such as Funduscopy, Ultrasound Biomicroscopy (UBM), and Optical Coherence Tomography (OCT), are difficult to perform. Conclusion: The underlying syndrome was suspected only after glaucoma occurred. Early detection and regular assessment play an important role in MPS. Routine follow-up is needed to ensure IOP control and determine the long-term outcome of IOP after trabeculectomy. Keywords: Glaucoma, Mucopolysaccharidosis, trabeculectomy